2023
DOI: 10.1097/ju.0000000000003079
|View full text |Cite
|
Sign up to set email alerts
|

Current Landscape of Surgical Assessment Models in Urology Residency Training

Abstract: Purpose:Assessing trainees’ surgical proficiency is an important aspect of urological surgical training. The current standard is the Urology Milestone Project, initially implemented in 2013. This evaluation is limited in that it contains only 3 questions on surgical competency per surgical modality with assessments occurring semi-annually without real-time operative feedback. However, since the Urology Milestones Project’s inception a plethora of competency-based surgical assessment tools have been described. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…It is a frequently performed but deceptively difficult urological procedure that requires experience and surgical skill to be performed optimally. 2 Our data evaluate patients who were all diagnosed with MIBC on initial resection 3 ; however, we strongly agree with Castaneda et al that if muscle was not present in the initial resection, repeat TURBT should always be performed in the setting of high-grade invasive tumor without muscularis propria to ensure adequate staging and diagnosis. Furthermore, our study adds to the growing body of literature suggesting that repeat TURBT prior to neoadjuvant chemotherapy does not improve survival outcomes 4,5 and potentially could result in inferior outcomes if repeat TURBT resulted in complications that resulted in delay of chemotherapy administration.…”
supporting
confidence: 81%
“…It is a frequently performed but deceptively difficult urological procedure that requires experience and surgical skill to be performed optimally. 2 Our data evaluate patients who were all diagnosed with MIBC on initial resection 3 ; however, we strongly agree with Castaneda et al that if muscle was not present in the initial resection, repeat TURBT should always be performed in the setting of high-grade invasive tumor without muscularis propria to ensure adequate staging and diagnosis. Furthermore, our study adds to the growing body of literature suggesting that repeat TURBT prior to neoadjuvant chemotherapy does not improve survival outcomes 4,5 and potentially could result in inferior outcomes if repeat TURBT resulted in complications that resulted in delay of chemotherapy administration.…”
supporting
confidence: 81%
“…Spin and its linguistic relative, the euphemism, are undermining our health care system. 2 With misinformation as rampant as it is, let us do more to protect urological literature. Otherwise, scientific manuscripts will begin to resemble tabloid journalism.…”
mentioning
confidence: 99%
“…However, we believe that relevant works were erroneously excluded, specifically 3 peerreviewed manuscripts presenting nonspecialtyspecific surgical assessment tools and 2 publications involving urological procedures, ie, robot-assisted radical prostatectomy and robot-assisted partial nephrectomy. [2][3][4][5][6][7] The papers describe performance metrics developed according to the rigorous process codified by the proficiency-based progression (PBP) training methodology. 8 As the first step, a core team of experts characterize the procedure/task, identifying its phases and operationally defined procedure events (ie, steps, errors, and critical errors).…”
mentioning
confidence: 99%
“…The metrics presented in the aforementioned studies were primarily developed as tools for training, with the aim of providing explicit, constructive, and formative feedback during deliberate practice teaching. [2][3][4][5][6][7] They are also used to assess the proficiency of trainees performing robotic surgical tasks or robot-assisted radical prostatectomy and robot-assisted partial nephrectomy procedures. Moreover, the tool developed to assess and train robotic suturing and knot tying skills was further validated in a prospective randomized and multicenter study including 48 trainees, which showed that the full PBP training pathway group performed better than the comparison groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation